The Effectiveness of Financial Incentives for Addressing Mangrove Loss in Northern Vietnam - Pham Thu Thuy; Vu, T.P.; Hoang, T.L.; Dao, T.L.C.; Nguyen, D.T.; Pham, D.C.; Dao, L.H.T.; Nguyen, V.T.; Hoang, N.V.H. (Frontiers Media, 2022)
This paper analyzes the effectiveness of existing financial incentives for mangrove conservation in Vietnam. Current conservation programs and projects have created financial incentives for mangrove protection, but the effectiveness of these incentives in addressing mangrove loss in northern Vietnam has been mixed. While financial incentives have contributed to a larger area of planted mangroves, their effectiveness is hampered by contradictory national policies, which encourage mangrove conservation on the one hand, and aquaculture expansion in mangrove areas on the other, thus making it difficult to address mangrove deforestation and degradation effectively. Mangrove conservation in Vietnam is challenged further by inequitable distribution of power and benefits, difficulties accessing information, weak law enforcement, lack of compliance, low payments for protecting mangroves, lack of full recognition of local rights, discontinued funding after policies and projects end, and lack of participation by local people in policy and project design and implementation. Conservation policies and projects should aim to protect existing mangrove forests, restore degraded mangroves and plant new ones to enhance mangrove area, quality and biodiversity. Sustainable mangrove conservation not only requires effective and sustainable financial incentives, but other enabling conditions such as addressing the conflict between mangrove conservation and aquaculture expansion, and grounding mangrove conservation projects by building on local knowledge and leadership. As these drivers are often motivated by national development goals and other sectoral development needs with ministries competing for budgets and influence, holistic land-use planning needs to be coupled with effective coordination and clarification of responsibilities between government agencies, and coordinated and consistent policies concerning these natural resources. Addressing these underlying governance issues is far more important for mangrove conservation and restoration than merely offering financial incentives as various national and international projects have attempted.